Salaries of Healthcare Professionals in the Republic of Croatia - Klarić, Ante; Švaganović, Marina; Cvitković, Miran (Medicine, Law & Society, 2020)
Salaries of healthcare professionals in the Republic of Croatia are regulated by a series of laws and regulations. A series of regulations defining the salaries and substantive rights of healthcare professionals cannot provide a clear, uniform and complete approach to regulating the subject matter of the law. In addition to the aforementioned issues of employment status, healthcare professionals originate from a standard that is similar and common to all public servants. In doing so, the legislature does not differentiate between a healthcare professional and his profession from an activity that deals with the protection of fundamental human values: the life and health of the individual. It is these core values that should inform not only governmental regulation of salaries and wages but also all other substantive rights, as a pledge for the smooth performance of such a highly responsible service through a clear, unambiguous and norm to precise them.
Keywords: salary; health worker; public service; health; legal norm